Interferon‐γ downregulates tight junction function, which is rescued by interleukin‐17A. Issue 12 (10th July 2021) - Mizutani, Yukiko; Takagi, Nao; Nagata, Haruna; Inoue, Shintaro
Abstract: Although atopic dermatitis (AD) has been reported to be a typical type 2 immune response disease, it is also an inflammatory skin disease that involves cytokines, such as Th1, Th17 and Th22. However, little is known about the mechanism by which the candidate cytokines, alone or in combination, are involved in AD pathology. Differences in cytokine balance, which contribute to the complexity of AD pathology, may influence the stratum corneum barrier function through tight junction (TJ) functional stability and contribute to disease severity. To confirm the regulatory mechanism of TJ protein expression in AD, we investigated the Th1 and Th17 pathways, which are the initiation factors of chronic AD pathology. We examined the effects of these cytokines on TJ protein expression in normal human epidermal keratinocytes in vitro, and also examined their function in a human skin equivalent model. We observed a time‐ and dose‐dependent inhibitory effect of IFN‐γ on claudin‐1 expression via the IFN‐γ receptor/JAK/STAT signalling pathway. IFN‐γ impaired TJ function in a human skin equivalent model. Moreover, we investigated co‐stimulation with IL‐17A, which is highly expressed in AD skin lesions and found that IL‐17A restores IFN‐γ‐induced TJ dysfunction. This restoration of TJ function was mediated by atypical protein kinase C zeta activation without recovery of TJ protein expression. These results are informative for personalized AD treatment via systemic therapies using anti‐cytokine antibodies and/or JAK inhibitors.